Association Between Living in Food Deserts and Cardiovascular Risk. Issue 9 (September 2017) - Kelli, Heval M.; Hammadah, Muhammad; Ahmed, Hina; Ko, Yi-An; Topel, Matthew; Samman-Tahhan, Ayman; Awad, Mossab; Patel, Keyur; Mohammed, Kareem; Sperling, Laurence S.; Pemu, Priscilla; Vaccarino, Viola; et al.
Abstract : Background—: Food deserts (FD), neighborhoods defined as low-income areas with low access to healthy food, are a public health concern. We evaluated the impact of living in FD on cardiovascular risk factors and subclinical cardiovascular disease (CVD) with the hypothesis that people living in FD will have an unfavorable CVD risk profile. We further assessed whether the impact of FD on these measures is driven by area income, individual household income, or area access to healthy food. Methods and Results—: We studied 1421 subjects residing in the Atlanta metropolitan area who participated in the META-Health study (Morehouse and Emory Team up to Eliminate Health Disparities; n=712) and the Predictive Health study (n=709). Participants' zip codes were entered into the United States Food Access Research Atlas for FD status. Demographic data, metabolic profiles, hs-CRP (high-sensitivity C-reactive protein) levels, oxidative stress markers (glutathione and cystine), and arterial stiffness were evaluated. Mean age was 49.4 years, 38.5% male and 36.6% black. Compared with those not living in FD, subjects living in FD (n=187, 13.2%) had a higher prevalence of hypertension and smoking, higher body mass index, fasting glucose, and 10-year risk for CVD. They also had higher hs-CRP ( P =0.014), higher central augmentation index ( P =0.015), and lower glutathione level ( P =0.003), indicative of increased oxidative stress. Area income and individual income, rather than food access, were associated with CVD risk measures. In a multivariate analysis that included food access, area income and individual income, both low-income area and low individual household income, were independent predictors of a higher 10-year risk for CVD. Only low individual income was an independent predictor of higher hs-CRP and augmentation index. Conclusions—: Although living in FD is associated with a higher burden of cardiovascular risk factors and preclinical indices of CVD, these associations are mainly driven by area income and individual income rather than access to healthy food. Abstract : Supplemental Digital Content is available in the text.